Vitamin therapy in the treatment of mild traumatic brain injury: new horizons of clinical practice - A. V. Shvets; K. V. Savichan; Ya. M. Klymenko (Український журнал військової медицини)
Objective: To investigate the main aspects of the impact of vitamin therapy on the treatment effectiveness of patients with mild traumatic brain injury and to illustrate it on the example of individual clinical cases.